Analisis Determinan Ergonomi dan Karakteristik Individu terhadap Keluhan Musculoskeletal Disorders (MSDs) pada Tenaga Kerja Bongkar Muat Pelabuhan - Mitahul Jannah; Linda Suwarni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Manual loading and unloading activities that still rely heavily on human labor may lead to musculoskeletal disorder (MSD) complaints due to static working postures, repetitive movements, and high physical workload. This study aimed to identify factors associated with MSD complaints among dock workers at PT Pelabuhan Indonesia II (Persero), Pontianak Branch. A cross-sectional design was used with a population of 101 workers and a sample of 50 workers. Data were collected in April–May 2023 and analyzed using the Chi-square test. The results showed significant associations between carrying position (p=0.000), length of employment (p=0.001), repetitive movements (p=0.004), and workload (p=0.009) with musculoskeletal complaints. However, working time was not significantly associated with musculoskeletal complaints (p=0.527). These findings suggest that ergonomic factors and cumulative work exposure play an important role in MSD complaints among dock workers. Therefore, the company is advised to implement preventive measures through occupational health and safety (OHS) training on safe work methods and correct working postures, educational outreach using posters or other media, and the provision of material-handling aids to reduce workers’ physical burden..